'Watch out, Sweetie': The Impact of Gender and Offence Type on Parents' Altruistic Fear of Crime. - Vozmediano, Laura; San-Juan, César; Vergara, Ana; Alonso-Alberca, Natalia (Sex Roles, 2017)
Altruistic fear of crime, that is, the fear that another person will become a victim of crime, is frequent and relevant, especially among parents for their children, but it has received much less attention than personal fear in the social sciences literature. We aim to analyze this fear in relation to a parent's gender, family gender composition (having sons only, daughters only or a mixed composition with both sons and daughters), and feared type of crime, with a sample of 290 parents from the Basque Country (north of Spain). A mixed-design ANCOVA showed no differences between mothers' and fathers' fears, but a statistically significant interaction was found between family gender composition and crime type. Parents in families with at least one daughter (daughters only and mixed families) reported more frequent fear than those in families with only sons, and fear was even more frequent when considering sexual abuse. Increased fear for daughters happens for all the considered crime types, even for those in which victims are usually boys. Findings highlight the relevance of parental fears even in objectively safe cities like the studied one, and they have implications for future studies on gendered transmission of fears and on related parental practices with impact on the autonomy and well-being of children.